2018
DOI: 10.5430/wje.v8n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Self-evaluation of Parental Competence – Differences Between Parents with Pedagogical and Non-Pedagogical Professions

Abstract: Parental competence is closely related to various factors, which can directly or indirectly influence parentalbehaviour. One of these factors is the level of education, and more recent research show that the parents' choice ofprofession can be favourable for the development of certain parental skills and experience of parental competence.The aim of this research was to determine if there is a difference in the sense of parental competence among parentsof pedagogical professions. Research was conducted on a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…One of the goals of the competent parent is to demonstrate to the child that he is genuine and sincere when he wants to understand his concerns or perspectives on certain things ( 122 ). Another goal of the competent parent is to identify what their child’s abilities, preferences, beliefs, or goals are and act accordingly ( 123 ).I.t has been demonstrated that the choice of a profession corresponding to the level of education determines the formation of parental skills through which parental competence is formed ( 124 ). Along with parental competence, parenting style is an important aspect for acquiring this competence ( 125 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the goals of the competent parent is to demonstrate to the child that he is genuine and sincere when he wants to understand his concerns or perspectives on certain things ( 122 ). Another goal of the competent parent is to identify what their child’s abilities, preferences, beliefs, or goals are and act accordingly ( 123 ).I.t has been demonstrated that the choice of a profession corresponding to the level of education determines the formation of parental skills through which parental competence is formed ( 124 ). Along with parental competence, parenting style is an important aspect for acquiring this competence ( 125 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, [5] proposes "the parents' choice of profession can be favorable for the development of certain parental skills and experience of parental competence". Parents apply their accumulated experience in different occupations to their children's education, and the education focuses, and effects are also different.…”
Section: The Impact From the Nature Of Parents' Occupationmentioning
confidence: 99%
“…Parents apply their accumulated experience in different occupations to their children's education, and the education focuses, and effects are also different. [5] also takes kindergarten and elementary school teachers as examples, thinking that they "better assess their parental efficacy and associate it with the experience of knowledge of how parental activity can affect a child and because of that knowledge can be a good behavior model for their children". Parents who are engaged in primary education have abundant educational knowledge, solid educational skills, a clear understanding of their educational abilities, and high educational expectations for their educational results so that they will invest more energy to provide a good education for children when carrying out education work.…”
Section: The Impact From the Nature Of Parents' Occupationmentioning
confidence: 99%